Black swan : The force of the unpredictable in modern society - Chvalina, Tomáš; Daňhel, Jaroslav, 1943-2025; Siuda, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This bachelor thesis describes the main problematics of Black Swan events and their effects on modern day society. The goal of this thesis is to define what are the characteristics of Black Swan and also searching for what is the best approach to isolate their dangerous attributes. To show the main problematics of Black Swan events, practical examples are used, with an emphasis in the most recent events of this type. The theoretical part focuses on the whole scheme of the problematics, main part being the analysis the financial crisis of 2008.
Vedoucí práce: Jaroslav Daňhel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses